Croatian Lexicography - Tadić, Marko (Array, 2006)
The article gives a survey of historical and contemporary Croatian lexicography. In addition to providing a summary of the most important Croatian dictionaries in the past, it gives an overall picture of lexicography today, not forgetting to mention the main corpus-building projects.